2022
DOI: 10.1371/journal.pone.0265989
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key genes and signaling pathways related to Hetian sheep wool density by RNA-seq technology

Abstract: Hetian sheep is a breed of sheep unique to the Hetian area of Xinjiang whose wool is used for producing blankets. Individual differences and hair follicle density are the key factors affecting wool production. Therefore, this study aimed to assess the Hetian sheep having different wool densities to statistically analyze the wool traits and hair follicle parameters. Furthermore, the transcriptome sequencing analysis was performed on the skins with different wool densities. The results showed that wool quantity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 60 publications
(50 reference statements)
1
9
0
Order By: Relevance
“…It affects hair follicle cell proliferation and the hair growth cycle [35]. Shi R et al showed that KIT may affect the growth and density of wool [36]. In this study, the expression levels of LncRNA MSTRG.98769.1 andMSTRG.84658.1 and the target genes FGF1, IGF1, and KIT in STH skin tissues were also significantly higher than those of SM.…”
Section: Discussionsupporting
confidence: 54%
“…It affects hair follicle cell proliferation and the hair growth cycle [35]. Shi R et al showed that KIT may affect the growth and density of wool [36]. In this study, the expression levels of LncRNA MSTRG.98769.1 andMSTRG.84658.1 and the target genes FGF1, IGF1, and KIT in STH skin tissues were also significantly higher than those of SM.…”
Section: Discussionsupporting
confidence: 54%
“…Of the two genes shown above to be expressed in Dani o, KRTAP4-12 is expressed in human hair follicles (see Additional file 3 : Table S1 and also Marquardt et al 2015) [ 23 ], while KRTAP16-1 is expressed in human skin and hair (Tissue expression of KRTAP16-1—Summary—The Human Protein Atlas), and is noted also as being expressed in the wool of Hetian sheep [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the two genes shown above to be expressed in Danio, KRTAP4-12 is expressed in human hair follicles (see File F2 of the Supplementary Materials and also Marquardt et al 2015) 22 , while KRTAP16-1 is expressed in human skin and hair (Tissue expression of KRTAP16-1 -Summary -The Human Protein Atlas), and is noted also as being expressed in the wool of Hetian sheep (Shi et al 2022) 23 .…”
Section: Expression Of Krtap Proteins In Non-mammalian Organismsmentioning
confidence: 99%